Factors Affect to Cosumer Choice Motives for Purchasing Pure Coffe in Dalat City - Anh, Nguyen Van; Hanh, Nguyen Thi Tuyet (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 3, 2019)
This research determines factors which affect consumer choice motives for purchasing pure coffee in Dalat City. The dissertation is executed through two means: qualitative research and quantitative research. The research results show that: “Choice Motive” positively impacts the “Subjective Norm” of customers, the “Purchase Attitude” of customers, and the “Perceived behavioral control” of customers. And the factors “Subjective Norm” of customers, “Purchase Attitude” of customers and “Perception behavior control” of consumers have a positive impact on the “Intention to purchase” pure coffee of  customers. The result of this research can used to reference in theory and reality through the basic argument of the behavior of consumers. From that, the author gives management implications for managers as well as limitations and directions for further research of the topic.